2016
DOI: 10.1093/intqhc/mzw144
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and associated mortality of central line-associated bloodstream infections at an intensive care unit in northern India

Abstract: Our results underscore the need for strict institutional infection control measures. Regular training module for doctors and nurses for catheter insertion and maintenance with a checklist on nurses' chart for site inspection and alerts in all shifts are some measures planned at our center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 29 publications
7
31
3
4
Order By: Relevance
“…(3-7) In the adult population, factors associated with CLABSIs include the site of CVC insertion and the duration of CVC use, the presence or absence of underlying disease, the severity score, the presence or absence of immunosuppression, the type of dressing used and whether an aseptic insertion technique is used. (8-11) However, information on factors associated with CLABSI in the pediatric population is limited, especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…(3-7) In the adult population, factors associated with CLABSIs include the site of CVC insertion and the duration of CVC use, the presence or absence of underlying disease, the severity score, the presence or absence of immunosuppression, the type of dressing used and whether an aseptic insertion technique is used. (8-11) However, information on factors associated with CLABSI in the pediatric population is limited, especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…First, this was a single-center, retrospective study that was subject to potential unmeasured confounding factors. Nevertheless, to date, it includes the largest cohort of patients with CVCs and suspected CRBSIs, and it includes more established prognostic factors than previous studies [ 11 , 25 ], as well as known sensitive indicators for the development of CRBSI [ 13 ]. Second, in this cohort, it was difficult to distinguish between delayed and prompt removal [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Brazilian study shows that the average length of ICU stay of 38.2 ± 28.8 days before the diagnosis of bloodstream-related infection, higher than that found in the present research9. Another study showed that the length of stay catheter longer than 10 days and in the ICU longer than 21 days are risk factors for central venous catheter-related infection [9][10][11][12] . Thus, the mean length of catheter stay found in the present study is below that reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that the incidence of obstructing thrombus ranges from 3% to 79% in central venous catheters. Signs of obstruction can be observed by stopping the infusion or when the alarm on the infusion pump occurs 10,11 . A Spanish study demonstrates that the occurrence of obstruction is directly related to the number of lumens of the catheter, with an incidence of obstruction of 4.96% [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation